Who cares about the democratic mandate of education? A text analysis of the Swedish secondary education reform of 2009 - Per Adman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2014)
For several decades after WWII, Swedish education reforms were justified extensively based on democratic and equality arguments. The Social Democrats, the party in governing power during this era, considered a uniform education system crucial to their endeavors towards a greater democracy and greater equality. According to current research, arguments of this kind are being used increasingly rarely to justify general reforms to public primary and secondary education. It is however unknown whether this is also true for the leftist/green opposition parties and not only the current center-right governing parties. The subject of this study is parliamentary debate and the text of the government bill concerning the latest key upper-secondary school reform of 2009, which entailed greater differentiation between students. Consequently, strong criticism from the leftist opposition from the democratic and equality perspectives was to be expected. On the contrary, this study shows that the opposition - like the center-right government - used democratic and equality arguments only to a minor extent. The results are consistent with fears, expressed with regard to Sweden and globally, that the democratic mandate is being ignored in the design of education systems for the future.
Keywords: I28; H75; 330; education reforms; Sweden; upper-secondary education; democratic arguments; equality arguments